El método de casos y el desarrollo del pensamiento crítico en estudiantes de ciencias sociales del cuarto grado de secundaria de la Institución Educativa 60024 San Juan de Miraflores, Iquitos 2023 - Rojas Garcia, Kim Abel (2025)
The central purpose of the research was to define the link between the case method and the development of critical thinking in students. The study worked with a quantitative approach with a cross-sectional correlational design. The population was made up of all 4th year high school students, who totaled 219 participants. A non-random sampling was carried out from which a sample of 67 students was extracted. The survey was used as a technique for collecting information, which allowed the questionnaire to be applied as a working instrument. The conclusion at an error level of 0.0% indicates the existence of a very strong compensation, which confirms that there is a statistically significant relationship between the case method and the development of critical thinking in students of the fourth grade of secondary education of the IEPSM N° 60024 San Juan de Miraflores Iquitos 2023.